Triple-Negative Mucinous Breast Carcinoma: A Case Report - Duizith, Ana Beatriz Bisol; Corrêa, Ana Carolina da Costa; Assef, Eloísa Talamini; Karvat, João Gabriel Vicentini; Costa, João Henrique e Silva; Gunther, Marina Guimarães; Magalhães, Maria Cristina Figueroa (Brazilian Journal of Case Reports, 2026)
Mucinous breast carcinoma (MBC) is a rare histological type, accounting for 1% to 6% of breast neoplasms. It is more frequent in older women and generally associated with a favorable prognosis. This paper reports on the case of a 52-year-old patient who initially presented with edema associated with mastalgia and nipple retraction in the left breast and was admitted to our service with only a routine mammogram. Initial staging examinations and biopsy with immunohistochemistry, followed by the need for panel expansion, initially suggested a primary site in the gastrointestinal tract; however, subsequent investigation revealed a primary triple-negative mucinous breast neoplasm. Thus, this report describes an uncommon case of triple-negative MBC, with few similar cases reported in the literature, as well as its diagnostic workup, definitive diagnosis, instituted treatments, and therapeutic response.